2021
DOI: 10.1101/2021.12.16.472906
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The genome sequence of the lesser marbled fritillary, Brenthis ino, and evidence for a segregating neo-Z chromosome

Abstract: The lesser marbled fritillary, Brenthis ino (Rottemburg, 1775), is a species of Palearctic butterfly. Male B. ino individuals have been reported to have between 12 and 14 pairs of chromosomes, a much reduced chromosome number than is typical in butterflies. Here we present a chromosome-level genome assembly for B. ino, as well as gene and transposable element annotations. The assembly is 411.8 Mb in span with contig and scaffold N50s of 9.6 and 29.5 Mb respectively. We also show evidence that the male individu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…While 34 chromosome pairs have been observed in Brenthis hecate spermatocytes (de Lesse 1961; Saitoh and Lukhtanov 1988), B. daphne and B. ino are reported to have only 12 -14 pairs of chromosomes (Maeki and Makino 1953;Saitoh et al 1989;Federley 1938;Saitoh 1987Saitoh , 1991. We recently assembled a B. ino reference genome (Mackintosh et al 2022) with 14 pairs of chromosomes. We found that a male individual was heterozygous for a neo-Z chromosome fusion and that the genome was highly rearranged compared to the ancestral nymphalid karyotype.…”
Section: Introductionmentioning
confidence: 99%
“…While 34 chromosome pairs have been observed in Brenthis hecate spermatocytes (de Lesse 1961; Saitoh and Lukhtanov 1988), B. daphne and B. ino are reported to have only 12 -14 pairs of chromosomes (Maeki and Makino 1953;Saitoh et al 1989;Federley 1938;Saitoh 1987Saitoh , 1991. We recently assembled a B. ino reference genome (Mackintosh et al 2022) with 14 pairs of chromosomes. We found that a male individual was heterozygous for a neo-Z chromosome fusion and that the genome was highly rearranged compared to the ancestral nymphalid karyotype.…”
Section: Introductionmentioning
confidence: 99%
“…The results of fusions between the ancestral sex chromosomes and autosomes are called neo-sex chromosomes (White, 1973; Hejníčková et al, 2021). Neo-Z chromosomes have been repeatedly described as occurring sporadically among different groups of Lepidoptera (Nguyen et al, 2013; Mongue et al, 2017; Mackintosh et al, 2021). More rarely, such sex chromosome – autosome fusions can be fixed in evolution and be the ancestors of entire phylogenetic lineages (Nguyen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The situation has changed quite recently due to the use of chromosome-level genome assemblies for karyotype analysis (Huang et al, 2022; Wang et al, 2022). This led to the first attempts to analyze rapid karyotypic evolution in different groups (Mudd et al, 2020; Yin et al, 2021), including Lepidoptera (Hill et al, 2019; Cicconardi et al, 2021; Mackintosh et al, 2021). However, to the best of our knowledge, no one has studied groups of organisms in which both evolutionary trends (chromosomal conservatism and chromosomal megaevolution) occur simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Two male individuals (MO IP 500 and MO IP 504) were collected with a hand net at Le Moulin de Bertrand, Saint-Martin-de-Londres, Montpellier, France and flash frozen in liquid nitrogen. High-molecular-weight (HMW) DNA was extracted from the thorax of one of these individuals (MO IP 504) using a salting out extraction protocol as described in Mackintosh et al . (2021).…”
Section: Methodsmentioning
confidence: 99%
“…Transposable elements (TEs) were annotated using the Earl Grey TE annotation pipeline (https://github. com/TobyBaril/EarlGrey, Baril et al 2021;Platt et al 2016;Wong and Simakov 2018;Smit et al 2015;Xu and Wang 2007;Ou and Jiang 2019;Rubino and Creevey 2014;Jurka et al 2005;Hubley et al 2015;Flynn et al 2020) as in Mackintosh et al (2021).…”
Section: Genome Annotationmentioning
confidence: 99%